2015
DOI: 10.1007/s13277-015-4155-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in human digestive tract malignancies

Abstract: Digestive tract malignancies, including oral, pharyngeal, esophageal, gastric, and colorectal cancers, are among the top 10 most common cancers worldwide. In spite of using various treatment modalities, cancer patients still suffer from recurrence and metastasis of malignant cells. Cancer stem cells (CSCs) are undifferentiated and highly proliferative malignant cells with unique properties mediated by overexpression of stemness markers, metastasis-related proteins, drug transporters, and DNA repair machinery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 247 publications
0
39
0
1
Order By: Relevance
“…The specificity and robustness of CD133 as a colorectal CSC marker may also need further investigation (36,37). The combinatorial use of other markers, such as CD44 and ALDH1, in colorectal cancers may better clarify CSC features and how p53 may affect stem cell characteristics of colorectal cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity and robustness of CD133 as a colorectal CSC marker may also need further investigation (36,37). The combinatorial use of other markers, such as CD44 and ALDH1, in colorectal cancers may better clarify CSC features and how p53 may affect stem cell characteristics of colorectal cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, among these genes are prominent markers of cancer stem cells, including CD24, PROM1 (or CD133), and EPCAM, all of which are associated with cancer “stemness” in gastrointestinal tumors. 29,30 This suggests that the unfavorable AC subtype might be driven, in part, by a stem cell-like phenotype. Indeed, this hypothesis is supported by the GSEA finding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have suggested that CSCs are closely related to tumor progression, metastasis, and processes of treatment resistance in GC [58]. Notably, recent research has demonstrated that CD44-positive tumor cells posses CSC properties, such as self-renewal and tumorigenicity, and the presence of CSCs is typically regarded as a marker of poor prognosis in patients with GC [59].…”
Section: Discussionmentioning
confidence: 99%